Inhibition of Interjacent Ribonucleic Acid (26S) Synthesis in Cells Infected by Sindbis Virus - Scheele, Christina M. (1969)
The interrelationship of viral ribonucleic acid (RNA) and protein synthesis in cells infected by Sindbis virus was investigated. When cultures were treated with puromycin early in the course of infection, the synthesis of interjacent RNA (26S) was preferentially inhibited. A similar result was obtained by shifting cells infected by one temperature-sensitive mutant defective in RNA synthesis from the permissive (29 C) to the nonpermissive (41.5 C) temperature. Under both conditions, the viral RNA produced appeared to be fully active biologically. Once underway, the synthesis of viral RNA in wild-type Sindbis infections did not require concomitant protein synthesis.